Influence of the oxygen content on the normal-state Hall angle in YBa2Cu3Oxn films - Wuyts, B.; Osquiguil, E.; Maenhoudt, M.; Libbrecht, S.; Gao, Z.X.; Bruynseraede, Y. (American Physical Society, 1993)
Fil: Osquiguil, E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Katholieke Univetsiteit Leuven; Bélgica